Sistem Pendukung Keputusan Pemilihan Kualitas Produk UPS Terbaik Menggunakan Metode Topsis dan SAW - Dimas Fathulyaqin; Ucuk Darusalam; Ira Diana Sholihati (Universitas Indraprasta PGRI Jakarta, 2021)
Every electronic device requires a good power supply so it perform functionally needed. Many devices use electrical energy. Starting from a laptop or computer device, TV, AC, refrigerator, cellphone, lights all use electric power. Even in every agency or company requires electrical energy for work activities to be more optimal. UPS (Uninterruptible Power Supply) itself is very useful for protecting electronic devices from blackouts that can occur at any time. This tool stores electrical energy such as battery and re-flows it, so that devices such as computers are not damaged. By using the calculation algorithm method TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) and SAW (Simple Additive Weighting) in making the best UPS quality decisions in terms of quality of goods by considering the quality of weight with the following criteria: Price, Capacity (VA), Capacity (Watts) and Runtime at 60W (min).